Clinical review of 24-35 year olds conceived with and without in vitro fertilization: study protocol - Sharon Lewis; Joanne Kennedy; David Burgner; Robert McLachlan; Sarath Ranganathan; Karin Hammarberg; Richard Saffery; David J. Amor; Michael M. H. Cheung; Lex W. Doyle; Markus Juonala; Susan Donath; et al. (BMC, 2017)
Abstract Background Children conceived by assisted reproductive technologies (ART) currently comprise 4% of Australian births. The manipulation of biological parameters related to fertilization and implantation are integral to successful ART but potentially pose a risk to the longer-term health of the offspring. There is consensus that many common adult health problems (particularly cardiovascular, metabolic and respiratory conditions) have their origins in early life, possibly before birth, and that risk trajectories track through childhood until clinical disease manifests in adulthood. Early life epigenetic variation may play a role in this process. However little is known about the long-term health of individuals conceived by ART. In a previous study, based on telephone-interviews, we found that young adults conceived by in vitro fertilization (IVF) had significantly more maternal reported atopic respiratory, endocrine, nutritional, and metabolic conditions than non-IVF conceived matched controls. Here we outline the protocol for a follow-up biomedical assessment of this cohort and a questionnaire to obtain information on potential confounders. Methods We are conducting a clinical review of an existing, well characterised cohort comprising 547 IVF-conceived adults and 549 matched controls. We are measuring cardiovascular intermediate phenotypes, metabolic parameters and respiratory function, complemented by epigenome-wide DNA methylation analysis. A pilot study demonstrated the feasibility of our proposed protocol and its acceptability to participants. Participants attend a 2-3 h clinical assessment and complete a study-specific online questionnaire. Measurements include: 1) cardiovascular phenotypes: carotid artery intima-media thickness and distensibility, retinal vascular calibre, resting blood pressure, pulse wave velocity and pulse wave analysis; 2) respiratory function: spirometry, plethysmography, multiple breath washout; 3) auxology: height, weight, waist circumference, bio-impedance. Blood is collected for 4) biomarkers of cardiometabolic profile including inflammatory markers and 5) epigenetic analysis. Discussion Recruitment for this clinical review is challenging as many of the participants have moved to regional, interstate or international locations. Additionally, many female participants are pregnant or breastfeeding, and are therefore ineligible. Nevertheless, comprehensive strategies have been developed to optimize recruitment. Given the increasing use of IVF and related technologies, the potential long-term consequences for risk of common adult diseases is an important clinical and public health issue.